Impact of slackline training & FIFA 11+ exercise program in preventing lower limb soft tissue injuries among semi-professional football players: a comparative study / Shibin Rag Panikare, Aparna Sudhan Mohana and Nizar Abdul Majeed Kutty - Panikare, Shibin Rag; Mohana, Aparna Sudhan; Majeed Kutty, Nizar Abdul (Universiti Teknologi MARA, 2023)
Elite semi-professional football showed a high incidence of soft tissue injury. The positive impact of slackline training on static and dynamic balance could indicate the usefulness of slackline training in injury prevention. The study aimed to compare the impact of slackline training and the FIFA 11+ exercise program on the Y-balance test to prevent soft tissue injuries in the lower limb among semi-professional football players. 30 subjects were recruited and randomly divided into 2 groups [Group A & Group B]. The Y-balance test score was assessed for all participants. Group A followed a supervised slackline training program, and Group B was involved in the FIFA 11+ exercise program. For both groups, the frequency of training was 3 days per week for eight weeks. On statistical analysis, the post-test values showed that the p-value of YBT AT, YBT PL, YBT PM scores between the 2 groups are < 0.05, < 0.01, and < 0.001 respectively. Though both groups showed improvement in Y-balance test scores, Group A showed significant improvement over Group B subjects. In conclusion, slackline training is a better method to improve dynamic balance and thereby prevent injuries than the FIFA 11+ exercise program.